Making Atmospheres - Bahmann, Dirk (Arts Research Africa, 2022)
This paper discusses a practical methodology, developed for a second-year architectural elective project, that aims to make tangible the qualities of architectural atmospheres. It argues for an embodied practice of making sculptural artefacts. It proposes that these can articulate and make apparent atmospheric qualities. To be able to imagine or recognise atmosphere is a crucial skill for architects since atmosphere determines how people respond to space. The methodology is designed, through iterative cycles of making and critical reflection, to make students increasingly aware of atmosphere and develop their ability to create and articulate certain feeling tones within spaces. This artistic praxis relies upon a nonlinear, bodily knowing that seeks to challenge the dominance of ocularcentric practice in the discipline of architecture.